Designing Universal and Intuitive Pictograms (UIPP) – A Detailed Process for More Suitable Visual Representations. Issue 163 (July 2022) - Bühler, Daniel; Hemmert, Fabian; Hurtienne, Jörn; Petersen, Christer
Highlights: Proposes a human-centered design process for universal and intuitive pictograms. Describes in detail each step and provides examples. Is scientifically grounded in semiotics, theories of intuitive interaction, and visual perception. Has been validated through empirical research and in practice. Can easily be followed by designers, researchers, and businesses. Abstract: Visual representations are perhaps the most important mode of human-computer and computer-mediated human-human interaction today. Nevertheless, we suggest, there is a lack of appropriate processes for their design. It seems, designers as much as researchers sometimes assume that visual representations are universally and intuitively comprehensible although evidence suggests otherwise, resulting in suboptimal designs. This article addresses the problem by proposing a human-centered design process for universal and intuitive pictograms. This process is grounded in semiotics, theories of intuitive interaction, and visual perception. Furthermore, it has been validated through empirical research and in practice. The article describes the process, it explains each step, and it provides examples. The result is detailed instructions that other designers, researchers, and businesses can adopt in their projects for designing more suitable visual representations.